Effect of Factor Xa Inhibitors on the Platelet-derived Microparticles Procoagulant Activity In Vitro> and In Vivo in Rats - Hérault, J. P.; Perrin, B.; Jongbloet, C.; Pflieger, A. M.; Bernat, A.; Herbert, J. M. (Thrombosis and Haemostasis, 2000)
The aim of this study was to investigate the effect of factor Xa inhibitors on the prothrombinase activity of platelet-derived microparticles in vitro and in vivo. The factor Xa inhibitors studied were DX9065A (a direct factor Xa inhibitor) and Sanorg34006 (an antithrombin (AT)-mediated factor Xa inhibitor). Microparticles formed from the platelet surface following activation were isolated by size exclusion gel chromatography. After purification, their presence was detected by their procoagulant activity and by flow cytometry. Our results show that factor Xa and/or factor Va were present at the surface of the platelet-derived microparticles. Prothrombinase formed on the microparticles was inhibited by factor Xa inhibitors at IC50 values of 0.45 ± 0.05 and 0.045 ± 0.005 µM for DX9065A and AT-Sanorg34006 respectively. In an experiment aimed at determining the kinetics of microparticles formation we demonstrated that thrombin traces were sufficient to induce the formation of a significant quantity of microparticles. Both factor Xa inhibitors delayed the formation of microparticles by delaying thrombin generation. The thrombogenic effect of the microparticles were studied in vivo in a modified arterio-venous shunt model in the rat. In this model, the increase in the thrombus weigh due to microparticles or phospholipids did not differ significantly (33% and 23% respectively). In these conditions, prothrombinase activity seemed to play a lesser role in the thrombogenic effect than phospholipids. Nevertheless, factor Xa inhibitors were efficient and inhibited thrombus formation in a dose-dependent manner.These results demonstrate that platelet-derived microparticles display a potent prothrombotic effect in vivo and show that factor Xa inhibitors are potent antithrombotic compounds when thrombosis was induced by microparticles.
Keywords: Factor Xa; microparticles; platelets; Sanorg34006; DX9065A